Case report on appendicitis with intraluminal ascariasis - Anduamlak B. Tiruneh; Marlon F. Machado; Thaddee Ngoy; Julian Forero-Millan (Radiology Case Reports)
Appendicitis commonly causes abdominal surgical emergencies, occurring with an incidence of 7%-14%. In tropical regions where it is endemic, ascariasis ranks as the most prevalent helminth infection. Intestinal helminths move through the digestive system and can block the appendix lumen, resulting in appendicitis due to luminal obstruction. In this case, we present an 8-year-old female who experienced periumbilical pain that shifted to the right lower abdomen over 3 days. She also vomited and lost her appetite. An abdominal ultrasound confirmed appendicitis, but the ultrasound did not visualize the cause of the obstruction. During surgery, doctors discovered intraluminal ascariasis as the cause of the obstruction and associated inflammation.